Arthurian Legend in Popular Culture - Foersterová, Veronika (Univerzita Pardubice, 2024)
The thesis focuses on the analysis of the transformations of Arthurian legends in modern film and television adaptations, specifically The Sword in the Stone, Monty Python and the Holy Grail, Excalibur, and Merlin. The aim is to analyse how the selected adaptations reinterpret Arthurian legends and analyse the changes in role of magic, magical objects, the role of the Druid, and how they deal with gender and social issues.
Artušovská legenda v populární kultuře
Keywords: artušovské legendy; magie; adaptace; feministická kritika; marxistická kritika; Excalibur; Merlin; genderové role; sociální struktury; Arthurian legends; magic; adaptation; feminist criticism; Marxist criticism; Excalibur; Merlin; gender roles; social structures